Impact of community extension program on the residents of barangay Catadman-Manabay - Dilao, Anilou Bayron (2011)
This paper evaluated the impact of the community extension programs on the residents of Barangay Catadman-Manabay, and helped diagnose on what are the programs that need further improvements. A descriptive-evaluative method was used out the Sixteen respondents who believed that the extension program has enhanced their skills as recipients of LSU's Community Extension Service. The respondents believed that LSU's extension programs have contributed a lot to the partner community on enhancing the skills and augmented the income of the residents. The respondents also perceived the necessity of improving the community extension programs of La Salle University especially the programs of SHM and College of Education. The trainings must be planned, organized and systematically be implemented in order to have great impact to the clienteles and to the community. Also needs assessment survey from must be done first in order to suit the ineterest of the clienteles.
Keywords: Community service; Community involvement